1994
DOI: 10.1128/aem.60.12.4478-4486.1994
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Molecular Characterization of Xanthomonas campestris Strains Causing Diseases of Cassava ( Manihot esculenta )

Abstract: Fifty-one strains representing Xanthomonas campestris pv. manihotis and cassavae and different pathovars occurring on plants of the family Euphorbiaceae were characterized by ribotyping with a 16S+23S rRNA probe of Escherichia coli and by restriction fragment length polymorphism analysis with a plasmid probe from X. campestris pv. manihotis. Pathogenicity tests were performed on cassava (Manihot escuknta). Histological comparative studies were conducted on strains of two pathovars of X. campestris (vascular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Probes. Membranes were hybridized with a plasmid probe, designated as pthB (previously named pF3), and two repetitive DNA elements, pBS6 and pBS8, previously characterized (40). Probe pthB is a 5.4-kb EcoRI fragment that was cloned from an indigenous plasmid and harbors a pathogenicity gene related to the avr/pth gene family (39).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Probes. Membranes were hybridized with a plasmid probe, designated as pthB (previously named pF3), and two repetitive DNA elements, pBS6 and pBS8, previously characterized (40). Probe pthB is a 5.4-kb EcoRI fragment that was cloned from an indigenous plasmid and harbors a pathogenicity gene related to the avr/pth gene family (39).…”
Section: Methodsmentioning
confidence: 99%
“…manihotis strains (40). Results revealed that the African strains are homogeneous, whereas in South America the pathogen is highly diverse (40). This is to be expected, because the Manihot genus originates from South and Central America, where the centers of diversity are in Brazil and Mexico (29).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Fifty‐two isolates collected in Colombia from different locations were grouped into four groups of virulence after inoculation onto three cultivars (Anonymous, 1987). Isolates also showed differences in the speed of symptom development, suggesting variation in aggressiveness (Verdier et al ., 1993, 1994). More recently, 10 pathotypes were defined among 91 Xam isolates in Venezuela, using five cassava cultivars as differentials (Verdier et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Strains of Xam have shown di¡erences in the speed of symptom development, suggesting variation in aggressive-ness [4^6]. Although some nonpathogenic Xam strains have been characterized genetically and phenotypically, little is known about the epidemiological importance of such strains in CBB disease [5,7]. When comparing a pathogenic Xam strain with a nonpathogenic derivative strain, an 8-kb deletion was localized on plasmid DNA of the nonpathogenic strain (V.V., personal communication).…”
Section: Introductionmentioning
confidence: 99%